The importance of support for psychophysical functioning of caregivers of loved ones with Alzheimer’s disease - Gałuszka, Aleksandra (Journal of Education, Health and Sport, 2021)
Neurodegenerative diseases are congenital or acquired progressive diseases of the nervous system. Their pathology involves the loss of nerve cells, and the essence of the disease process leads to the appearance of multiple symptoms of neurological damage, related to motor function (e.g. ataxia) and memory (dementia). The process leading to the appearance of symptoms of neurodegenerative disease begins well before they appear. It often takes place over many years and may be asymptomatic. The first symptoms appear when a significant number of neurons are damaged or when a specific part of the central nervous system is affected. One of the neurodegradative diseases is Alzheimer’s disease . It mainly affects people over the age of 65 and affects 5-7% of the population. Its duration is about 8-14 years. The specificity of the disease is a gradual and irreversible disruption of the body’s homeostasis, cognitive processes and progressive memory loss, which leads to visual-spatial orientation disorders. Emerging apraxia results in inability to use everyday tools. In the late stage, the dementia is very severe and the memory is often limited only to autobiographical facts. Speech disorders are so advanced that the patient can only speak single words. Emotional disturbances also occur, manifested by apathy or aggressiveness. The disorder also includes problems with chewing, swallowing, and sphincter control. The presence of the disease in the family structure causes many changes and sacrifices on the part of family members.